Integration of Transcriptomic and Proteomic Profiles Reveals Multiple Levels of Genetic Regulation of Taproot Growth in Sugar Beet (Beta vulgaris L.) - Li, Ningning; Zhang, Yongfeng; Wang, Xuefeng; Ma, Huailong; Sun, Yaqing; Li, Guolong; Zhang, Shaoying (Frontiers in Plant Science, 2022)
Sugar beet taproot growth and development is a complex biological process involving morphogenesis and dry matter accumulation. However, the molecular regulatory mechanisms underlying taproot growth and development remain elusive. We performed a correlation analysis of the proteome and transcriptome in two cultivars (SD13829 and BS02) at the start and the highest points of the taproot growth rate. The corresponding correlation coefficients were 0.6189, 0.7714, 0.6803, and 0.7056 in four comparison groups. A total of 621 genes were regulated at both transcriptional and translational levels, including 190, 71, 140, and 220 in the BS59-VS-BS82, BS59-VS-SD59, BS82-VS-SD82, and SD59-VS-SD82 groups, respectively. 10, 32, and 68 correlated-DEGs-DEPs (cor-DEGs-DEPs) were significantly enriched in the proteome and transcriptome of the BS59-VS-BS82, SD59-VS-SD82, and BS82-VS-SD82 groups, respectively; which included ribonuclease 1-like protein, DEAD-box ATP-dependent RNA helicase, TolB protein, heat shock protein 83, 20 kDa chaperonin, polygalacturonase, endochitinase, and xyloglucan endotransglucosylase/hydrolase (XTH). Additionally, Beta vulgaris XTH could enhance the growth and development of Arabidopsis primary roots by improving cell growth in the root tip elongation zone. These findings suggested that taproot growth and expansion might be regulated at transcriptional, posttranscriptional levels, and also may be attributed to cell wall metabolism to improve cell wall loosening and elongation.